The Effect of Using Sorting Activity Strategy on Preparatory School Students’ Performance in English - Alawi, ISSA Kahlil; Sultan, Amra Ibrahim (Journal of Tikrit University for Humanities, 2021)
The purpose of study is to measure the effect of using sorting activity strategy (SAS) on preparatory school students’ performance in English .On the other hand this strategy is related to teaching pronunciation of vocabulary for EFL preparatory school students in the classrooms , since sorting words help students to perform the pronunciation of word correctly as well as help them to know the meaning of vocabulary through open sort and closed sort and also through minimal pairs . From this lunched ,this study may explores ways to support teachers’ attitudes toward English teaching and also to integrate the process of education . Using this strategy encourages students to understand and memorize more numbers of vocabularies into classrooms.